Commensurability oscillations in a periodically modulated phosphorene. (11th September 2017) - Tahir, M; Vasilopoulos, P
Abstract: The recent experimental realization of high-quality phosphorene leads to novel electronic and optical properties with possible new device applications due to its huge direct band gap. We study the commensurability or Weiss oscillations in monolayer phosphorene in the presence of a weak perpendicular magnetic field B and a weak and periodic, electric or magnetic one-dimensional modulation. Either modulation broadens the Landau levels into bands, whose width oscillates with B, and the oscillations appear in the electrical conductivity perpendicular to the modulation taken along the direction ( x ) of the smaller effective mass. Compared with the oscillations of the diffusive conductivity in a two-dimensional electron gas (2DEG) for typical electron densities n e ∼ 10 15   m − 2, the ones in phosphorene, with typical n e ∼ 10 16   m − 2, have approximately similar height but a period significantly smaller when plotted versus 1 / B while plotted versus B they occur at significantly higher fields. The Shubnikov–de Haas oscillations exhibit a similar behaviour. When the modulation is taken along the direction ( y ) of the larger effective mass, the oscillation period is close to that of a 2DEG. For equal modulation strengths the bandwidth due to a magnetic modulation is one order of magnitude larger than that due to an electric one and the amplitude of the oscillations in the diffusive conductivity about 50 times larger. Numerical results are presented for experimentally relevant parameters.